METHODS OF DANGER ANALYSIS - Запорожець O. I.; Гладкая, Л. А. (Proceedings of National Aviation University (archive), 2021)
The generalized model of the analysis of dangers on the basis of use of the theory of probability for definition of risks of dangerous factors and consequences of their influence is considered.